PENGELOLAAN DAN PENYIMPANAN UANG KAS MASJID: ANALISIS KUALITATIF PEMILIHAN JASA PERBANKAN SYARIAH DAN KONVENSIONAL - Mursidah, Rifqah; Islamiyah, Nurul; Rusanti, Ega; Sofyan, A Syathir (Jurnal Ar-Ribh, 2021)
The purpose of this study is to determine the perception of mosque takmir in terms of financial management and storage of mosque funds, both in conventional banking and Islamic banking. Research carried out is a qualitative study with field research (field studies) in the deepening of the reference as a source of primary and secondary data. The results showed that the lack of socialization from sharia banking and the lack of knowledge of mosque takmir about sharia banking resulted in mosque takmir still managing and storing mosque funds in conventional banking.Keywords: Takmir Masjid, Mosque Finance, Islamic Banking.